Experimental models of coarse-clast transport by tsunamis - Oetjen, Jan; Schüttrumpf, Holger; Engel, Max (Geological records of tsunamis and other extreme waves, 2020)
This chapter summarizes background and setup of wave-flume experiments investigating boulder transport by tsunamis. It emphasizes both opportunities for better understanding boulder transport in natural settings and limitations, i.e., the sources of uncertainty, related to these experiments. It also reviews the most important findings published so far, explains linkages with numerical models, and draws conclusions on research directions and open questions, which need to be tackled in future studies.